Nocturia treatment outcomes: Analysis of contributory frequency volume chart parameters. Issue 1 (31st March 2017) - Epstein, Matthew; Blaivas, Jerry; Wein, Alan J.; Weiss, Jeffrey P.
Abstract : Aims: Our aim is to determine which changes in frequency volume chart (FVC) parameters are associated with nocturia improvement. Methods: This is a real life retrospective analysis of FVC's of men who were treated for nocturia and completed at least two 24 h FVC's. Patients were divided into two groups—an improved cohort defined by a decrease of ≥1 nocturnal void from baseline and a non‐improved cohort. Results: A total of 414 FVC's were analyzed (207 baseline and 207 post treatment) among a cohort of 105 men. Baseline nocturia severity (ANV, 3.5 vs. 2.3, respectively) and nocturnal urine volume (NUV, 880 mL vs. 650 mL) was greater in the improved cohort compared to the non‐improved cohort. The improved cohort had a decreased 24 h volume (−310 vs. +120 mL), and NUV (−290 vs. +170 mL) compared to the non‐improved cohort. At the followup visit, the improved cohort experienced a statistically significant decline in ANV (−1.8 vs. +1.0). No significant difference was seen in baseline 24 h volume or bladder capacity (MVV), though patients in the improved cohort experienced a small decrease in MVV. First uninterrupted sleep period (FUSP) increased significantly in the improved cohort (+1.8 h), and dropped (−0.6 h) in the non‐improved cohort. Conclusions: Improvement in nocturia was associated with a decrease in both 24 h voided volume and NUV, but not MVV, suggesting that improved patients consumed less fluid. The increase in FUSP in the improved cohort demonstrates the potential for nocturia therapies to improve impaired sleep architecture.